2004
DOI: 10.1515/jaots-2004-0105
|View full text |Cite
|
Sign up to set email alerts
|

Methane Conversion into C2 Hydrocarbons and Carbon Black in Dielectric-barrier and Gliding Discharges

Abstract: The methane conversion into C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In this work, the two graphite electrodes were substituted with two tungsten electrodes, and the origin of the carbon precursor was the carbon black which comes from the decomposition of the benzene in the reactor. Benzene was used as the origin of the carbon precursor because the hydrocarbon (benzene, methane, acetylene, ethylene) has no influence on the products' properties [9] and the experimental device can be simplified.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the two graphite electrodes were substituted with two tungsten electrodes, and the origin of the carbon precursor was the carbon black which comes from the decomposition of the benzene in the reactor. Benzene was used as the origin of the carbon precursor because the hydrocarbon (benzene, methane, acetylene, ethylene) has no influence on the products' properties [9] and the experimental device can be simplified.…”
Section: Introductionmentioning
confidence: 99%
“…for removal of hydrocarbons, NO x , soot, etc. from engine exhaust and for cleaning industrial waste gases [33][34][35][36][37][38][39]. Our earlier investigations have shown that GD can be coupled with the action of solid catalysts for accelerating the decomposition of some pollutants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of nonequilibrium plasma lies in its nonequilibrium property: it has a high electron temperature (10 4 -10 5 K), whereas the gas temperature remains low (as low as room temperature), which leads to some unusual chemical performance. Direct methane conversion using discharge plasmas to syngas, 21 acetylene or other C 2 hydrocarbon, 12,[14][15][16]19,20 liquid fuels (methanol or higher hydrocarbons), 8,23 and oxygenates (such as acids and alcohols) [8][9][10][11] have been extensively investigated. Especially, direct synthesis of oxygenates and liquid fuels from methane using nonequilibrium plasmas has recently attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also been conducted simultaneously to exploit other nonconventional conversion technologies. Among the nonconventional technologies under development, the nonequilibrium plasma is very promising. …”
Section: Introductionmentioning
confidence: 99%